A Not Quite Robust Enough Political Economy. Issue 3 (1st October 2016) - Gamble, Andrew
ABSTRACT: Mark Pennington's Robust Political Economy cogently defends a "classical liberal" position that frankly acknowledges market imperfections and failures. However, Pennington's preoccupation with the comparative advantage of markets over states, in terms of epistemics and incentives, leads him into a cul-de-sac. The comparison rests on a sharp dichotomy between state and market that overlooks the fact that the state is itself a "spontaneous order" that evolved alongside, and codependent with, the market. Thus, Pennington's argument is incoherently conservative in defending whatever exists, which must have evolved—but in excluding the state from this Panglossian vision. Consequently, Pennington continues the unfortunately antipolitical tendencies of modern-day classical liberals, who treat politics as alien territory rather than as the ground on which the form of state and market alike are shaped.